Vorbemerkungen: Zentralität als geographischer, mentaler und virtueller Begriff - Herbers, Klaus; Melville, Gert; Blennemann, Gordon (Die Ordnung der Kommunikation und die Kommunikation der Ordnungen. Bd. 2 Zentralität: Papsttum und Orden im Europa des 12. und 13. Jahrhunderts, 2013)
Num Pages: 331

Le nécrologe du livre du chapitre de l’abbaye Saint-Pierre-aux-Nonnains de Metz (BNF lat. 10028) Commentaire et édition - Blennemann, Gordon (École nationale des chartes, 2009)

Altestamentarische Modelle für den populus christianus: Hrabanus Maurus' Kommentar zu den Makkabäerbüchern 1 und 2 - Blennemann, Gordon (Vom Blutzeugen zum Glaubenszeugen?: Formen und Vorstellungen des christlichen Martyriums im Wandel, 2014)

Basilica-monasterium: A Comparative Study of the First Holy Sites of Western Christianity, c. 400-c. 900, I - Blennemann, Gordon; Helvétius, Anne-Marie; Veronese, Francesco (2023 International Medieval Congress, 2023)
Historiography of ancient monastic trends has been deeply renewed during the recent years thanks to several conferences which put forward comparative and interdisciplinary approaches, some of them being specifically dedicated to female forms of religious life. Henceforth, scholars dissuade us to read the history of monasticism trough 'Benedictine glasses'. They invite us to take into account every type of sources - written, archaeological, iconographic, epigraphic. The interpretation of the written sources - monastic rules, but also hagiographical and diplomatic sources - has been nowadays deeply renewed. These recent works agree to give to early 'monasticism' a wider definition, taking into account the extreme diversity of the community forms of religious life attested in the West during this period. These works deserve to be continued further through comparative studies focused on precise problematics. This research project aims to explore how some communities tried to reconcile the practice of a monastic life with the service of an important sanctuary, and also how some ancient communities succeeded in holding firm through centuries, often with the support of powerful protectors.

Croyances et pratiques sociales dans les sermons de Césaire d’Arles - Blennemann, Gordon (RELIER : revue interdisciplinaire d’études religieuses, 2023)
En dialogue avec des recherches récentes menées sur les identités multiples des chrétiens de l’Antiquité tardive, cette contribution propose un cas d’étude sur les sermons adressés au peuple de l’évêque gaulois Césaire d’Arles (vers 470-542), plus précisément sur ceux dans lesquels Césaire aborde les pratiques de ses contemporains face à l’abondance d’enfants et l’infertilité, leurs pratiques de guérisons et leurs cultures festives en lien, notamment, avec les fêtes des saints. Miroirs de situations communicationnelles précises, ces sermons permettent de saisir, malgré leur aspect rhétorique, les tensions existant entre le discours épiscopal de Césaire traitant des enjeux de pastorale et de pouvoir épiscopal d’une part, et l’adhésion des chrétiens à des pratiques sociales, jugées incompatibles avec une identité chrétienne d’autre part. Ces sermons montrent en filigrane l’existence d‘une opposition entre deux modèles d’organisation de références identitaires : un modèle pyramidal qui classe toutes les références identitaires par rapport à la seule christianité versus un modèle latéral de ces mêmes références qui suppose qu’en fonction de situations quotidiennes concrètes, la christianité revêtait, pour les croyants, une importance variable. Ce cas d’étude ne permet pas seulement de souligner l’importance d’un regard scientifique équilibré sur les croyances et les pratiques, mais aussi les limites d’une classification de pratiques jugées tantôt religieuses, tantôt sociales.

Die Ordnung der Kommunikation und die Kommunikation der Ordnungen. Bd. 2 Zentralität: Papsttum und Orden im Europa des 12. und 13. Jahrhunderts - Andenna, Cristina; Blennemann, Gordon; Herbers, Klaus; Melville, Gert (Franz Steiner Verlag, 2013)
Das Papsttum und die vita religiosa, die Welt der Klöster und Orden, sind die beiden einzigen institutionellen Lebensformen des Mittelalters, die für sich eine eigene universelle Geltung beanspruchen konnten. Durch die Ausbildung komplexer kommunikativer Strukturen und innovativer Organisationsformen nahmen beide vor allem seit dem 12. und 13. Jahrhundert Anteil an der Grundlegung eines "Kulturraums Europa".Vor diesem Hintergrund stand der analytische Vergleich von Papsttum und vita religiosa als aufeinander bezogene Kommunikationssysteme im Mittelpunkt zweier Tagungen am Deutsch-Italienischen Zentrum für Europäische Exzellenz der Villa Vigoni, deren Ergebnisse nun in einer zweibändigen Publikation vorliegen.Die Beiträge des zweiten Bandes widmen sich der Rolle der römischen Kurie bei der überregionalen Vermittlung religiöser Normen und kultureller Werte als universal gedachte Ordnungsvorstellungen und fragen zugleich nach dem Anteil der religiösen Orden an diesen Vermittlungsprozessen.
Pages: 331
Keywords: Europa; Geschichte; Kommunikation; Papsttum

Das Martyrium als Denkfigur: Brüche und Entwicklungslinien in christlicher Perspektive - Blennemann, Gordon; Herbers, Klaus (Vom Blutzeugen zum Glaubenszeugen ? : Formen und Vorstellungen des christlichen Matyriums im Wandel, 2014)
Section: 1 vol. (319 p.) ; 24 cm.

Die Darstellung und Deutung des Räumlichen im hagiographischen Dossier der Hl. Glodesindis, Äbtissin in Metz (BHL 3562–3564) - Blennemann, Gordon (Heilige, Liturgie, Raum, 2010)
OCLC: ocn642845040
Keywords: Christian saints; Congresses; Cult; Liturgies; Sacred space; Sanctification; Worship

Raumkonzept und liturgische Nutzung: Eine Spurensuche zur Frühgeschichte der Metzer Frauenklöster Sainte-Glossinde und Saint-Pierre-aux-Nonnains - Blennemann, Gordon (Frauen-Kloster-Kunst: Neue Forschungen zur Kulturgeschichte des Mittelalters Beiträge zum Internationalen Kolloquium vom 13. bis 16. Mai 2005, anlässlich der Ausstellung "Krone und Schleier", 2007)

Antiques vierges et nouvelles normes. L’hagiographie comme discours normatif chez les bénédictines de Metz (IXe-XIe siècle) - Blennemann, Gordon (Cahiers de civilisation médiévale. Xe-XIIe siècle, 2024)
Cet article propose d’aborder la question de l’implication des communautés de femmes de Metz dans les mouvances de réforme en Lorraine du ixe et surtout du xe siècle et xie siècles, par le biais des récits hagiographiques et, dans une moindre mesure, historiographiques. Ces communautés sont au nombre de trois : Sainte-Glossinde, Saint-Pierre-aux-Nonnains et Sainte-Marie-aux-Nonnains. L’article part de l’hypothèse que ces récits constituent autant de contributions à une communauté discursive débattant, en contexte de réforme, de la définition de la vita religiosa féminine. Les démarches argumentatives adoptées par leurs auteurs recourent entre autres à des modèles de vie ascétique très anciens, notamment celui des vierges et matrones à vocation ascétique de l’Antiquité tardive.
ISBN: 9782490783168 Number: 265
Keywords: Antiquité tardive; Carolingiens; Lorraine; Metz; Saint-Pierre-aux-Nonnains; Sainte-Glossinde; Sainte-Marie-aux-Nonnains; hagiographie; monachisme féminin; réforme lotharingienne

Continuities and Transformations in Hagiography - Blennemann, Gordon; Helvétius, Anne-Marie (Rethinking Reform in the Latin West, 10th to Early 12th Century, 2023)
Section: Rethinking Reform in the Latin West, 10th to Early 12th Century
Keywords: Church History; History; History of Religion; Medieval History; Religious Studies

Liturgy and Female Monastic Hagiography Around the Year 1000: A lecture croisée of the Life of Liutrud, the Second Life of Glodesind of Metz and the So-called Pontificale Romano-Germanicum - Blennemann, Gordon (Women and Monastic Reform in the Medieval West, c.100-1500 Debating Identities, Creating Communities, 2023)
In a fundamental essay published in 1991 on the significance of religious women’s communities in early and high medieval Saxony, the late Michel Parisse called for a comparative perspective on the political, social and religious conditions of the conspicuous density of women's communities in Saxony. In doing so, he referred to his home region of Lorraine, for which he – amongst others – used the term Lotharingia to describe its early medieval reality. In terms of sheer numbers, Lotharingia is indeed closest to the Saxon situation, but chronologically its monasteries also refer back to earlier times. Examples of this are the Merovingian foundations of Remiremont in the Vosges and Sainte-Glossinde and Saint-Pierreaux- Nonnains in the Carolingian lieu de mémoire Metz. Women's monasteries like these combined stabilising power in the Carolingian core lands with supra-regional influence within the framework of the Frankish regnum and imperium. For areas such as Saxony, which were integrated comparatively late into the Frankish sphere of influence, the politico-religious structures of the ancient parts of the Frankish realm provided a framework of tradition and reference far into the post-Carolingian period. In this contribution – not least as an expression of gratitude to one of my academic teachers – I would like to take up Parisse's observations. I do not aim at a similarly broad investigation, especially since a comparative approach in a broad thematic perspective would go beyond the scope of the contribution as well as of this volume, even though recent studies on women's religious communities in Saxony and Lorraine invite us to do so. The focus is rather on a partial aspect: the textual and ideological relations between liturgy and hagiography in the tenth and early eleventh centuries. Such an approach is complementary to studies in which the importance of relics and hagiographical texts as vectors of communication, the transfer of ideas and the spatial integration of new secular and ecclesiastical structures of power were elaborated – again primarily for the Carolingian period. Following on from these studies, the observations in this article concentrate on religious and monastic aspects of these genres and raise questions about the shared significance of liturgy and hagiography for the definition and mediation of traditional as well as new ascetic and monastic models of life in the tenth century. The debates which shaped these models are part of monastic and broader religious transformations traditionally labelled as the reform of the tenth and early eleventh century.

Martyre et prédication. Adaptations d’un modèle hagiographique dans les sermons de Césaire d’Arles - Blennemann, Gordon (Normes et hagiographie dans l'occident latin, VIe-XVIe siècles: actes du colloque international de Lyon 4-6 octobre 2010, 2014)

Le religieux comme vecteur d’étude du haut Moyen Âge : perspectives d’enquête pour l’hagiographie et la liturgie - Blennemann, Gordon (Théologiques : revue interdisciplinaire d’études religieuses, 2019)
Cet article propose d’explorer l’importance du phénomène religieux comme vecteur de compréhension du monde médiéval. Dans une perspective d’enrichissement de l’échange entre les disciplines intéressées par le phénomène religieux, il souhaite familiariser les étudiants et les chercheurs en dehors du champ de l’histoire médiévale avec quelques tendances passées et actuelles de la recherche, notamment des travaux intéressés par une étude du religieux à l’intersection du politique et du social. En complément de ces observations préliminaires, l’article trace quelques pistes de réflexion pour les champs de recherche de l’hagiographie et de l’histoire du culte des saints et celui de l’histoire de la liturgie, en focalisant sur le haut Moyen Âge occidental.

Konstanz und Wandel : religiöse Lebensformen im europäischen Mittelalter - Blennemann, Gordon; Kleinjung, Christine; Kohl, Thomas (Didymos-Verlag, 2016)
Section: 1 v. (280 pages) : illustrations ; 25 cm

Eine Bildurkunde aus dem Benediktinerinnenkloster Sainte-Glossinde in Metz. Zugleich ein Beitrag zur mediävistischen Bild- und Objektwissenschaft - Blennemann, Gordon (Konstanz und Wandel: religiöse Lebensformen im europäischen Mittelalter, 2016)
Section: 1 v. (280 pages) : illustrations ; 25 cm

Hagiographie : une norme narrée. Regards sur les Vitae de Jutta de Sponheim et d’Hildegarde de Bingen et le Liber visionum d’Élisabeth de Schönau - Blennemann, Gordon (Enfermements. II, Règles et dérèglements en milieu clos (IVe-XIXe siècle), 2015)
D'évidence, il n'y a pas d'enfermement sans règle. L'un des traits communs aux mondes clos est que ceux qui y vivent doivent obéir à des normes fortes, qu'il s'agisse de la règle monastique, de la règle hospitalière ou du règlement de prison. Reprenant l'étude comparée des enfermements religieux et carcéraux esquissée par les sciences sociales dans les années 1960 et 1970, le présent ouvrage, qui fait suite au volume Enfermements. Le cloître et la prison (VIe-XVIIIe siècle) publié en 2011, explore la place que prennent les règlements et les normes dans les cloîtres comme dans les prisons. Par une méthode comparée systématique, il montre toutes les nuances de cette histoire sur la longue durée, entre ive et XIXe siècles, et dans toute l'Europe, des Iles Britanniques à la péninsule ibérique. À cet effet, il interroge la nature de la règle et historicise sa mise en texte, avant de comparer les modes de production de l'obéissance et les dérèglements qui surgissent dans les milieux clos. L'un des enjeux de cette étude comparée des règles et dérèglements en milieux clos est de comprendre et de réévaluer le rôle que la discipline régulière religieuse a pu jouer dans la mise en place des systèmes carcéraux occidentaux
Section: 459 pages ; 24 cm.

Heiligkeit und Devianz in vormodernen Kontexten : Perspektiven einer möglichen Systematisierung - Blennemann, Gordon (Sakralität und Devianz : Konstruktionen – Normen – Praxis, 2015)
Section: 1 vol. (314 p.) : Ill. ; 24 cm.

Vom Blutzeugen zum Glaubenszeugen ? : Formen und Vorstellungen des christlichen Matyriums im Wandel - Blennemann, Gordon; Herbers, Klaus (Franz Steiner verlag, 2014)
In zahlreichen Glaubenskontexten gilt das individuelle oder kollektive Selbstopfer als unüberbietbarer Weg, Grundüberzeugungen durch das Blut als Opferleistung zu besiegeln. Im Christentum werden so die Märtyrer zu wichtigen Zeugen vor Gott, stehen sie doch in der Schar der Heiligen an erster Stelle. Die Autorinnen und Autoren des E-Books widmen sich vor diesem Hintergrund dem Martyrium als historischem Phänomen. Die epochenübergreifende Perspektive richtet den Blick auf die Ursachen seiner langfristigen Wirkmächtigkeit als Denkfigur. Die spätantiken Grundlagen von Martyriumskonzeptionen und deren Tradition und Vermittlung in Mittelalter und Neuzeit werden ebenso untersucht wie Wandlungsprozesse in der Darstellung der Figur des Märtyrers. Denn über dessen Bedeutung als personifiziertes Glaubensideal bestand über Jahrhunderte hinweg Konsens, auch wenn der Märtyrer gerade in Konfliktsituationen von konkurrierenden Parteien als Leitfigur instrumentalisiert werden konnte. So eröffneten sich vielfältige Perspektiven der Adaption und Rekontextualisierung des Martyriums, die in den einzelnen Beiträgen ergründet werden.
Section: 1 vol. (319 p.) ; 24 cm.

Venantius Fortunatus, Vita Radegundis - Blennemann, Gordon (Le légendier de Turin : ms. D.V.3 de la Bibliothèque nationale universitaire, 2014)
Section: 891 pages : illustrations + 1 DVD-ROM

Papsttum und Orden in der Interaktion. Beobachtungen und Perspektiven zur begrifflichen Einordnung - Blennemann, Gordon; Andenna, Cristina (Die Ordnung der Kommunikation und die Kommunikation der Ordnungen. Bd. 2 Zentralität: Papsttum und Orden im Europa des 12. und 13. Jahrhunderts, 2012)
OCLC: ocn845099532
Keywords: Communication; Communication systems History; Congresses; History; Monasticism and religious orders; Papacy

Die Metzer Benediktinerinnen im Mittelalter: Studien zu den Handlungsspielräumen geistlicher Frauen - Blennemann, Gordon (Matthiesen Verlag, 2011)

Ascetic Prayer for the Dead in the Early Medieval West - Blennemann, Gordon (The Cambridge History of Medieval Monasticism in the Latin West, 2020)